Effect of Individual Characteristics, Self-Efficacy, and Entrepreneurial Motivation on Entrepreneurship Interest through Entrepreneurial Attitude - Suci Ramadoan; Soussou Raharimalala; Salim Diarra (Indonesian Journal of Business and Entrepreneurship Research, 2024)
This study examines the influence of individual characteristics, self-efficacy, and entrepreneurial motivation on entrepreneurial interest through entrepreneurial attitude among students of the Faculty of Economics and Business (FEB) at Universitas Negeri Makassar. Using a quantitative explanatory approach, data were collected from 102 respondents through purposive sampling and analyzed with Path Analysis. The results show that individual characteristics and entrepreneurial motivation indirectly influence entrepreneurial interest through entrepreneurial attitude, while self-efficacy has no significant direct effect. Additionally, entrepreneurial attitude positively affects entrepreneurial interest. This study offers valuable insights for educators and lecturers to mentor students in developing entrepreneurial skills, emphasizing both product management and marketing strategies. It also encourages students to enhance their business decision-making abilities. Future research can explore additional variables and methodologies to expand the understanding of factors influencing entrepreneurial interest.